(untitled) - Mitchell, Paul Q. (Boston, MA., 2002)
Practical information on the equipment and tools needed for the veterinarian who wants to expand his practice to include dentistry* extensively illustrated: includes x-rays, photographs of procedures, and photographs of pathological conditions * provides important information on home care recommendations that the practitioner can share with pet owners
Keywords: Veterinary dentistry